2001
DOI: 10.1094/cchem.2001.78.3.261
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Amylose Content on Expansion of Extruded Rice Pellet

Abstract: Cereal Chem. 78(3):261-266Rice pellets were prepared by single-screw extrusion cooking with an in-barrel water content of 50 wt%. Three different types of rice, indica glutinous, japonica, and indica, were used as raw materials. Reconstituted rice flour was made to study the effect of amylose content on pellet expansion. The glass transition (T g ) and expansion (T e ) temperatures of extruded pellet were determined by differential scanning calorimetry (DSC) and noncontact infrared thermometer, respectively. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 20 publications
0
12
0
5
Order By: Relevance
“…This could be explained by a collapse of the expanded structure due to delayed product solidification, due to lower glass transition temperature, Tg. However, Chen and Yeh (2001) showed that Tg was not affected by amylose content. Consequently, we can assume that this limit of expansion is rather due to the type of morphology acquired by proteins, and to the higher level of amylopectin.…”
Section: Relation Between Extrusion Parameters and Physicochemical Prmentioning
confidence: 94%
“…This could be explained by a collapse of the expanded structure due to delayed product solidification, due to lower glass transition temperature, Tg. However, Chen and Yeh (2001) showed that Tg was not affected by amylose content. Consequently, we can assume that this limit of expansion is rather due to the type of morphology acquired by proteins, and to the higher level of amylopectin.…”
Section: Relation Between Extrusion Parameters and Physicochemical Prmentioning
confidence: 94%
“…(3)) was applied to the DSC and DMTA data of the blends studied, so as to predict the effect of water on their glass transition temperatures. Even though this equation was originally deduced for binary polymer mixtures, its use has been extended to more complex mixtures such as starchy flours, by taking water as solvent and the remaining components as solids or solutes (Chen & Yeh, 2001;Cuq & Icard-Vernière, 2001;Sandoval et al, 2009):…”
Section: Glass Transition Temperatures Of Cs-co Blend Effect Of Moismentioning
confidence: 99%
“…In a complex food matrix water competition among different food components will always be present. Values of K presented in the literature for complex systems, have been reported to vary between 3.4 and 5.5 for wheat durum semolina (Cuq & Icard-Vernière, 2001), 4.2 for rice flour (Chen & Yeh, 2001), and K values ranging of 2.2-3.8 were found for cereal starchy materials such oat flour, rice flour, oat-rice flour blend and a ready to eat cereal breakfast formulation as reported by Sandoval et al (2009). These reported K values are in the same order of magnitude than those obtained here (Table 2).…”
Section: Glass Transition Temperatures Of Cs-co Blend Effect Of Moismentioning
confidence: 99%
“…There are many parameters that affect the degree of swelling, normally related to both the composition of the raw material (Chen and Yeh 2001;Jones et al 2000) and processing conditions (Chandrasekhar and Chattopadhyay 1990;Owusu-Ansah et al 1984). Expansion of the DIC-textured cheese snack products was depended on the saturated steam pressure (which determined the vessel temperature) and the processing time.…”
Section: Physical Characterizationsmentioning
confidence: 99%